Peran Guru Bimbingan Konseling dalam Mengatasi Tindakan School Bullying Sebagai Upaya Mewujudkan Sekolah Ramah Anak di SMA S Xaverius Bukittinggi - Adinda Adinda; Yeni Afrida; Lorenchia Braferi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2024)
This research aims to explain the role of guidance and counseling teachers in dealing with school bullying in schools as part of efforts to build child-friendly schools at SMA S Xaverius Bukittinggi. In addition, this study also tries to identify and analyze the challenges faced in this process. The theory used in this research is the role theory proposed by Biddle and Thomas. This research methodology uses a qualitative approach, specifically using descriptive qualitative methodology. The data collection methods used in this study were interviews, observation, and documentation. The findings of this study highlighted the important role of teachers in overcoming the problem of school bullying in schools at SMA S Xaverius Bukittinggi. This includes formulating effective policies to address school bullying in schools, identifying the main causes of such behavior, implementing appropriate disciplinary measures, forming study groups, delivering persuasive messages to both the perpetrator and other students, providing counseling and guidance services, offering incentives or rewards, implementing programs that promote the prevention of school bullying in schools, conducting regular supervision and monitoring, and fostering a nurturing and supportive environment conducive to students' well-being. Challenges faced include managing student behavior outside the school environment.